(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
From the verybeginning Handloom products held a stable position in Indian economy whichprovided economically sound living standard as well as employment to the ruraland semi urban Indian inhabitants especially. The year 1991 marked theemergence of different names in this arena which led to a tough marketing ofhandloom products in exports and an easy way to get into the domestic markets.There is a large customer base in India, where it becomes necessary to takeimmediate steps to tap the domestic market as well as exports. While the marketis very competitive at the low end of the value chain, firms are not takingadvantage of the large domestic market in generating economies of scale todeliver cost advantage in export markets. Hence, this study make the SWOTanalysis of Handloom Industry.